2018
DOI: 10.3389/fimmu.2018.00032
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Short NFATc1/αA Isoform Interferes with Peripheral B Cell Differentiation

Abstract: In lymphocytes, immune receptor signals induce the rapid nuclear translocation of preformed cytosolic NFAT proteins. Along with co-stimulatory signals, persistent immune receptor signals lead to high levels of NFATc1/αA, a short NFATc1 isoform, in effector lymphocytes. Whereas NFATc1 is not expressed in plasma cells, in germinal centers numerous centrocytic B cells express nuclear NFATc1/αA. When overexpressed in chicken DT40 B cells or murine WEHI 231 B cells, NFATc1/αA suppressed their cell death induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…While we detected an enrichment signal for 45 TFBS in 12 B cell-associated modules. Only two TFs (MYC and NFATC1) have their TFBS enriched in their own modules [119][120][121][122], supporting a network model of TFs regulating the transcription of genes in distinct co-expressed gene sets, which is consistent with current literature [19][20][21]132].…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…While we detected an enrichment signal for 45 TFBS in 12 B cell-associated modules. Only two TFs (MYC and NFATC1) have their TFBS enriched in their own modules [119][120][121][122], supporting a network model of TFs regulating the transcription of genes in distinct co-expressed gene sets, which is consistent with current literature [19][20][21]132].…”
Section: Plos Onesupporting
confidence: 88%
“…It has been shown that MYC is necessary to stimulate both proliferation and inhibited differentiation in mature B cells induced by BCR signal [119,120]. BCR signaling is also known to increase the transcription of the NFACT1 gene, which in turn plays an important role in controlling plasmablast/plasma cell formation [121,122].…”
Section: Transcriptional Control Of Genes Within B Cell Modulesmentioning
confidence: 99%
“…ET formation by MCs was later described in response to other GAS strain ( 131 ), or to other extracellular bacteria. For example, by HMC-1 in contact with Pseudomonas aeruginosa ( 130 ), HMC-1 or BMMCs co-cultured with S. aureus ( 132 ), or BMMCs infected with Enterococcus faecalis ( 133 ).…”
Section: Antimicrobial Roles Of Mast Cellsmentioning
confidence: 96%
“…In human BL cells transcription of the NFATc1 gene is mainly driven by the P1 promoter, whereas P2 promoter activity is dominant in mouse BCL tumors and derived cell lines (Figures 4A, B). This might reflect the different origin of human BLs, which arises from GC B cells where NFATc1/a isoforms are expressed (36), and murine BCL tumors that originate at earlier stages of B cell development (Figures S3A, B).…”
Section: Discussionmentioning
confidence: 99%